Synthesis of the All-l Cyclopentapeptides Versicoloritides A, B, and C - Kaur, Harveen; Heapy, Amanda M.; Brimble, Margaret A. (Synlett, 2012)
Herein we describe the first synthesis of the all-l naturally occurring cyclopentapeptides versicoloritides A, B, and C. We found that the extent of oligomerization and epimerization upon head-to-tail cyclization of the linear pentapeptide precursors could be reduced to acceptable levels by modifying the reaction conditions.
Keywords: cyclic peptides; versicoloritides; natural products; cyclization; total synthesis